Building spaces for citizen participation and collaboration. Library and information services - Cárdenas, Celia Mireles; Arana López, Gladys N.; Peña Landeros, Jorge Alejandro (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
The concept of Open Government is supported on three foundations: Transparency, Collaboration, and Participation. Libraries are democratic spaces that encourage social cohesion and guarantee equal opportunities for information access. Despite the implications of the digital communication era, the construction of libraries is still underway. Also and to a greater extent, their design incorporates spaces that lead to social interaction and freedom of expression among their communities. This becomes relevant for academic libraries since they have an impact on training critical citizens who are also committed with their environment. This investigation employs a mixed research methodology describing the situation of academic library buildings in Mexico, with an emphasis on collaborative work spaces in the libraries of the Autonomous University of San Luis Potosí.